ANALISIS PERBANDINGAN KINERJA INVESTASI EMAS DAN INVESTASI SAHAM SELAMA MASA INFLASI 1994 - 2013 - WAHYUNI, ASRI NUR (JURNAL BISNIS STRATEGI, 2014)
AbstractThis purpose  of this research is to analyze the causal relationship between gold return  and stock market return as well as the influence of the two variables and the effect of inflation as a macroeconomic   variable to gold return  and stock  market return.  This research was conducted to determine the best investment choice between gold investments  dan stock investments during time of inflation from 1994 – 2013. During the research period occurs phenomenon in which relationships between variables are not in accordance with the theories that have been proposed.  This is upported by the differences in the results of several previous  researches.This study is done by using the monthly data of gold price, JCI and inflation end of each month during the period January 1994 – December 2013. Methods of analysis used in this study using VAR estimation  model  by using the optimal lag test, stationary test, Johansen cointegration test, Granger causality  test, IRF and  analysis  of VD.This results  of this research showed no causal relationship between gold returns  and stock market returns. Based on the estimated  VAR models  it is known that in the short term gold returns  have no effect on stock  market returns  and vice versa as well as the inflation variable does not affect the return of gold and stock market returns. Johansen cointegration test results show there is a long – term relationship between the three variables. IRF analysis  results indicate that stock market return is convergent  and has no effect permanently. These results  were confirmed  by the results  analysis of VD which  shows  that the gold returns reached stability in the fifth period after the shock is given, while the stock market returns in the sixth period. It can be concluded that the movement that occurs in gold investment does not cause movement of the stock investment and they do not have a relationship of mutual influence and variable inflation has not effect on them. In the end, it is known that gold investment is the best option compared to stock investment during times of inflation.